2013
DOI: 10.1155/2013/745836
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Race Effect: Resistant to Instructions

Abstract: The cross-race effect (CRE) is the tendency for eyewitnesses to be better at recognizing members of their own race/ethnicity than members of other races/ethnicities. It manifests in terms of both better discrimination (i.e., telling apart previously seen from new targets) and a more conservative response criterion for own-race than for other-race faces. The CRE is quite robust and generally resistant to change. Two studies examined the effectiveness of reducing the CRE with special instructions given prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Although the feature instructions resulted in a comparable decrease in false alarms for White and African American faces-suggesting an overall criterion shift, rather than a selective shift depending on face racethis finding is consistent with the more general principle that instructions about the CRE given prior to encoding can moderate performance (Hugenberg et al, 2007;Young et al, 2010), at least under some conditions (for failures of instructions to moderate the CRE, see Bornstein et al, 2013;Tullis et al, 2014). Similar effects have been obtained by directing observers to more diagnostic features (Hills & Pake, 2013) or constraining the amount of a face that they can view (Caldara et al, 2010), which suggests that efforts to reduce or eliminate the CRE through training have the potential to be successful (Brigham, 2008).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although the feature instructions resulted in a comparable decrease in false alarms for White and African American faces-suggesting an overall criterion shift, rather than a selective shift depending on face racethis finding is consistent with the more general principle that instructions about the CRE given prior to encoding can moderate performance (Hugenberg et al, 2007;Young et al, 2010), at least under some conditions (for failures of instructions to moderate the CRE, see Bornstein et al, 2013;Tullis et al, 2014). Similar effects have been obtained by directing observers to more diagnostic features (Hills & Pake, 2013) or constraining the amount of a face that they can view (Caldara et al, 2010), which suggests that efforts to reduce or eliminate the CRE through training have the potential to be successful (Brigham, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Recent research has demonstrated considerable support for encoding-based factors in the CRE (e.g., Bornstein, Laub, Meissner, & Susa, 2013;Evans, Marcon, & Meissner, 2009;Hancock & Rhodes, 2008;Meissner, Brigham, & Butz, 2005). Rather than a simple difference in time spent encoding own-race versus other-race faces, they appear to be processed differently (Tullis, Benjamin, & Liu, 2014).…”
mentioning
confidence: 99%
“…However, it is quite plausible that the effects of such manipulations may be limited or eliminated in circumstances where the encoding efficiency of cross-race faces is experimentally limited. For example, making stimuli harder to recognize (e.g., cropping stimuli; using different stimuli at encoding and recognition, Bornstein, Laub, Meissner, & Susa, 2013), using stimuli that are perceptually similar (naturally occurring or via morphing), or otherwise eliminating individuating characteristics that are easier for inexpert perceivers to extract from targets (e.g., using Greebles; Gauthier & Tarr, 1997) could potentially attenuate or eliminate motivational effects. Similarly, truncated exposure times may prevent the deployment of motivated resources (e.g., or efficient modes of face processing (e.g., Palermo & Rhodes, 2002), further limiting the ability of motivation to influence encoding.…”
Section: How Do Perceiver Motives and Experience Coact In Creating Anmentioning
confidence: 99%
“…The 14 initial presentation photographs depicted young men and women in their early 20s wearing their own clothes and smiling; each photograph was in color, homogeneous in lighting and size, and included their head and shoulder (Bornstein, Laub, Meissner, & Susa, 2013;Doob & Kirshenbaum, 1973;Evans et al, 2009). The ratio of male to female photographs was constant across race.…”
Section: Photographs For Initial Presentation and Lineupsmentioning
confidence: 99%
“…The MEI is a 23-item scale that measures individuals' past and present interactions with other racial/ ethnic groups, which has been used in prior ORB research (e.g., Bornstein et al, 2013) and is described as a measure of affiliation with other races, as opposed to preferences for other races (Zane & Mak, 2003). Higher scores on the MEI indicate more interactions with people of other groups.…”
Section: Independent Measuresmentioning
confidence: 99%